Application of Direct Learning Model to Improve Student Learning Outcomes on Digestive System Materials in Class XI Science 2 SMA Negeri 7 Southeast Maluku - Sisilia Domitila Sangur; Helen J. Lawalata; Zusje W. M. Warouw (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aimed to describe students' learning outcomes using the Direct Instructions Learning Model on the digestive system material. This study is classroom action research. This study was conducted in class XI of SMA Negeri 7 Southeast Maluku. The subjects of this study were 22 students of class XI IPA. The study results showed that the percentage of classical learning completion in cycle I was 32% with an average score of 63.5% and cycle II was 82% with an average score of 80.22. With these research results, it can be concluded that applying the direct instructions learning model can improve student learning outcomes on the digestive system material in class XI of SMA Negeri 7 Maluku Tenggara.